Students’ Satisfaction Index on Chemistry Learning Process (Jurnal Pendidikan IPA Indonesia, 2019)
This study was aimed at describing the index of students’ satisfaction in the chemistry learning process in SMAN 4 Singaraja Bali Indonesia and the factors that influenced it. For that, the survey research was conducted. The population was all students of the tenth and eleventh-grade students of groups of mathematics and natural sciences in academic year 2016/2017 in SMAN 4 Singaraja Bali consisting of 478 people. All population members became samples. Data were collected using a questionnaire. The numbers of respondents which returned the questionnaire were 431 people. Data the were analyzed by descriptive statistics. The results of the study showed that the index of students’ satisfaction viewed from a dimension of tangible, reliability, responsiveness, assurance, and empathy was 86.24%, 85.67%, 87.42%, 88.11%, and 85.18%, respectively, and all dimensions were quite high. Overall the index of students’ satisfaction in the chemistry teaching and learning process was 86.19% and it was high.